2010
DOI: 10.1007/s00436-010-2123-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of bloodmeals from biting midges (Diptera: Ceratopogonidae: Culicoides Latreille) in Denmark

Abstract: Culicoides vectors are critical to the survival and transmission of bluetongue virus as infection only occurs in areas or regions where competent vectors are present. The success of Culicoides biting midges as vectors is mainly related to their vast population sizes and to their means of dispersal. Their choice of host for blood feeding is sparsely described. The aim of the present study was to establish methods for the identification of bloodmeal hosts and determine the identity and diversity of bloodmeals of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 26 publications
6
83
3
Order By: Relevance
“…C. obsoletus also seemed to be attracted to heifer, goat and ewe, as well as birds (Viennet et al, 2013), although this species is considered to be strictly mammalophilic (Lassen et al, 2012). While some Culicoides species are opportunistic, most Palaearctic species appear to prefer cattle (Bartsch et al, 2009;Lassen et al, 2011;Ninio et al, 2011). Ninio et al (2011) identified the blood of horse, rabbit, pig, sheep and human in the abdomens of blood-fed C. obsoletus females, whereas Pettersson et al (2013) observed the blood of sheep, cattle and horse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…C. obsoletus also seemed to be attracted to heifer, goat and ewe, as well as birds (Viennet et al, 2013), although this species is considered to be strictly mammalophilic (Lassen et al, 2012). While some Culicoides species are opportunistic, most Palaearctic species appear to prefer cattle (Bartsch et al, 2009;Lassen et al, 2011;Ninio et al, 2011). Ninio et al (2011) identified the blood of horse, rabbit, pig, sheep and human in the abdomens of blood-fed C. obsoletus females, whereas Pettersson et al (2013) observed the blood of sheep, cattle and horse.…”
Section: Discussionmentioning
confidence: 99%
“…In general, many hematophagous species (such as mosquitoes and Culicoides) prefer a specific host on which they will feed (Kettle, 1962;Bartsch et al, 2009;Votypka et al, 2009;Lassen et al, 2012;Viennet et al, 2013), although some species are known to be generalists (Blackwell et al, 1994). Some Culicoides species, however, exhibit opportunistic feeding behaviour with respect to host distribution and density (Kettle, 1977;Garros et al, 2011;Lassen et al, 2011Lassen et al, , 2012Calvo et al, 2012). Visual stimuli and body odour are the two main elements involved in attraction to hosts (Bishop et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphological characters are not reliable enough to identify to species level females of the C. obsoletus complex. However, (a) in the Canary Isles, where we conducted the experiment 2, only C. obsoletus and Culicoides analis have been found (Delécolle 2002), (b) only C. obsoletus males have been captured in the study area (authors personal observations) and (c) biting midge species belonging to the "obsoletus complex" including C. obsoletus and Culicoides scoticus, trapped near livestock farms, are capable of feeding on birds such as mallards and common wood pigeons (Lassen et al 2010). Therefore, although the biting midges were not attracted by bird secretions but by the UV light, this is not because pigeons are not potential hosts for these species.…”
Section: Discussionmentioning
confidence: 99%
“…In general, however, its development sites still remain poorly documented (Szadziewski 1985). Females of C. obsoletus are known to attack livestock and humans (Szadziewski 1985), but they can also readily feed on birds (Lassen et al 2011). This very common and widely distributed species is susceptible to infection with BTV-8 and BTV-9, therefore it is considered to be a probable vector of the bluetongue virus in Europe (Carpenter et al 2008).…”
Section: Commentsmentioning
confidence: 99%